Reportagem, memória e história no jornalismo brasileiro - Bergamo, Alexandre [UNESP] (FapUNIFESP (SciELO), 2011)
The present article explores how recent changes in journalism have redefined the way in which the area's professionals see themselves in the present and so how they see their past, their own 'history.' I draw from my own and other ethnographies of journalism, particularly those focused on the editorial office, in order to examine the specificity of 'news' and especially 'reporting' as a historical 'document,' a discussion essential to understanding the link between 'journalistic memory' and 'national memory.' The text also discusses the effects that the imposition of a 'journalistic style,' the need for formal qualifications and the reorganization of the work market have had - and continue to have - on the increasingly systemized organization and description of careers now considered emblematic in the profession.
Keywords: Culture; Culture industry; Journalism; Memory; Style manuals